Enhanced Basicity of Ag2O by Coordination to Soft Anions. Issue 5 (28th January 2015) - Ren, Bo; Wang, Meiyan; Liu, Jingyao; Ge, Jiantao; Dong, Hai
Abstract In Ag2O‐mediated benzylation, the addition of a catalytic amount of KI can greatly improve reactivity. This is usually attributed to the formation of a more reactive iodo‐substituted electrophile. However, our studies show this to be due to the enhanced basicity of Ag2O through coordination of soft iodide anions to the silver atom, and show KI to be an initiator. A catalytic amount of Ag2O and NaBr can catalyze transesterification reactions, indicating the enhanced basicity of Ag2O by bromide. We believe that this is a general effect for metal oxides and soft anions, applicable to a wider range of organic reaction systems.